Legal and Political Rights Advocacy in Wrongful Conviction Death Penalty Cases in China: A Study of the Leping Case of Injustice - Jue, Jiang (Columbia Journal of Asian Law, 2016)
The problem of wrongful conviction has become more widely acknowledged in China today. Drawing on a study of the Leping case of injustice, in which four defendants were convicted of rape and murder and sentenced to death for a crime they had not committed, this article discusses how the efforts of correcting it meet a deadlock in China’s judicial system, and how, in this circumstance, Chinese civil society initiates and runs a network advocacy aiming at breaking the deadlock and advancing the correction.